RELIGIO-CULTURAL APPROACH TO THE GENDER PROBLEM IN INDIA - Anand, Sri. (Journal of Dharma, 1988)
Apart from the general progressive trends of modern political life and society - of scientific and rational thinking and high technological advancement, expanding into a kind of world civilization, beyond all caste, creed and gender - side by side, rather along with these, there are many growing parallel incidents also of narrow superstitions, religious beliefs and fanaticism. And these erupting primitive character of our own history have acquired a new name "Fundamentalism," that is to say, political terrorism and religious fundamentalism have acquired a new significance, it seems, in our so-called modern life also in some recent past. The sacrifice of Rup Kanwar as seti in Rajasthan, of late has acquired also some social, political and sacerdotal importance. The event has evoked immense interest in all quarters including some historical and cultural researchers. Dr. Romila Thapar writes: "There is no simple explanation for the origin of the custom of burning widows on the pyres of their dead husbands. It is said to be a symbol of aristroctic status associated with many early societies such as those of the Greeks and the Scvthians." She also mentions that "In the Rig Veda the act was only a mimetic ceremony. The widow lay on her husband's funeral pyre before she was raised from it by a male relative of her dead husband.